Aplikasi Metode EOQ untuk Pengendalian Inventory Perusahaan Furnitur CV XY Nganjuk - Rony Kurniawan; Muhammad Zuhdi Sasongko (Yos Soedarso Economic Journal (YEJ), 2024)
This research is about inventory to find out what size order is most economical. As a research subject for the Small and Medium Enterprises (UKM) furniture company CV XY Nganjuk. The data used is production raw material inventory series data from March 2023-March 2024. The objectives of this paper are: (1) Find out what number of orders for raw materials (teak wood) is the most economical for CV safe amount of inventory for CV XY Nganjuk. (3) What is the total inventory cost (Total Inventory Cost-TIC) for the CV XY Nganjuk company. The research method is descriptive with Economic Order Quantity (EOQ) calculations. This research produces an EOQ value of 4.85 cubic meters per order. The maximum inventory level or safety stock value is based on a maximum average value of 2.42 (cubic). The Reorder Point value is 4.5 cubic meters. Meanwhile, the total cost value generated is Rp130,104,000 every 12 months. Findings: in this study the economic order quantity was greater than the calculated value of the order quantity according to the company's calculations. The amount of safety stock is greater than the safety stock calculated by the company's ordering costs. (total cost) calculated by the company is smaller than the economic needs of TC.